Spoiling Tibet China and resource nationalism on the roof of the world - Lafitte, Gabriel (Asian arguments., 2013)
The mineral-rich mountains of Tibet, hitherto largely untouched by China's growing economy, are now to be the site of massive investment in copper, gold, silver, chromium and lithium mining for the world's factory, with devastating environmental and social outcomes. Spoiling Tibet is the first book that investigates mining at the roof of the world - an entirely unique authoritative guide through the torrent of online posts, official propaganda and exile speculation.